Comparison of the sedative and analgesic effects of butorphanol with acepromazine, midazolam, or dexmedetomidine following propofol induction and isoflurane maintenance in canines - KUMAR, RAJESH; AAKANKSHA; KUMARI, ARCHANA; VERMA, N K; SAXENA, A C; HOQUE, M (The Indian Journal of Animal Sciences, 2022)
Adequate sedation and excellent depth of analgesia were recorded in all the four groups after induction to the end of surgical procedure, however, significantly higher sedation score and depth of analgesia were observed in group D and significantly lower was observed in group A in comparison to other groups. Butorphanol with acepromazine, midazolam, or dexmedetomidine provides adequate sedation and analgesia in the dogs, before induction with propofol, so it made handling of the animals proper and safe before induction. Dexmedetomidine produces most profound sedation and analgesia followed by midazolam and acepromazine along with butorphanol.